Use of lanthanides to alleviate the effects of metal ion-deficiency in Desmodesmus quadricauda (Sphaeropleales, Chlorophyta) - Goecke, Franz; Jerez, Celia G.; Zachleder, Vilém; Figueroa, Félix L.; Bišová, Kateřina; Řezanka, Tomáš; Vítová, Milada (Frontiers in Microbiology, 2015)
Lanthanides are biologically non-essential elements with wide applications in technology and industry. Their concentration as environmental contaminants is, therefore, increasing. Although non-essential, lanthanides have been proposed (and even used) to produce beneficial effects in plants, even though their mechanisms of action are unclear. Recently, it was suggested that they may replace essential elements. We tested the effect of low concentrations of lanthanides on the common freshwater microalga Desmodesmus quadricauda, grown under conditions of metal ion-deficiency (lower calcium or manganese concentrations). Our goal was to test if lanthanides can replace essential metals in their functions. Physiological stress was recorded by studying growth and photosynthetic activity using a pulse amplitude modulation (PAM) fluorimeter. We found that nutrient stress reduced parameters of growth and chlorophyll fluorescence, such as maximal quantum yield, relative electron transport rate, photon capturing efficiency and light saturation irradiance. After adding low concentrations of five lanthanides, we confirmed that they can produce a stimulatory effect on microalgae, depending on the nutrient (metal) deprivation. In the case of a calcium deficit, the addition of lanthanides partly alleviated the effects, probably by a partial substitution of the element. In contrast, with manganese deprivation (and at even lower concentrations), lanthanides enhanced the toxic effect and severely inhibited growth. These results show that lanthanides can replace essential elements, but their effects on microalgae depend on stress and the physiological state of the microalgae, raising the possibility of environmental impacts at even low concentrations.